Combined role of thromboelastography and coagulation indicators in predicting thromboembolism risk in cancer patients - Huang, Liqiu; Dong, Wei; Hu, Xiaojie; Wang, Yu; Zhang, Lina (Frontiers in Medicine, 2025)
ObjectiveExploring the application value of thromboelastography (TEG) and four coagulation indicators in the risk assessment of thromboembolism (TE) in cancer patients.MethodsRetrospectively analyzed the clinical data of 160 cancer patients. Among them, 45 patients experienced thromboembolism (TE group) and 115 patients did not experience thromboembolism (non-TE group). We analyzed the levels of TEG and coagulation indicators in the two groups of patients and the risk factors for TE in cancer patients.ResultsThe Angle and MA of the thromboembolic group were significantly higher than those of the non-TE group, whereas K and R were significantly lower than those of the non-TE group (P < 0.05). D-dimer (D-D) and fibrinogen (FIB) levels in the thromboembolic group were significantly higher than those in the non-TE group, while activated partial thromboplastin time (APTT), prothrombin time (PT), and platelet count (PLT) were significantly lower than those in the non-TE group (P < 0.05). Binary logistic regression analysis confirmed that angle, maximum amplitude (MA), K, R, D-D, APTT, PT, and PLT were all important influencing factors for the occurrence of TE in cancer patients (P < 0.05).ConclusionsTEG and coagulation index level detection have high application values in the risk assessment of TE in cancer patients.